ChemInform Abstract: Emergence of the First Catalytic Oligonucleotides in a Formamide‐Based Origin Scenario. Issue 20 (April 2016) - Sponer, Judit E.; Sponer, Jiri; Novakova, Olga; Brabec, Viktor; Sedo, Ondrej; Zdrahal, Zbynek; Costanzo, Giovanna; Pino, Samanta; Saladino, Raffaele; Di Mauro, Ernesto
Abstract: Review: 97 refs.